Validation Process of New Behavior Management Technique during Local Anesthesia in Children with Dental Anxiety - Javanaiah, Nagarathna; Srinath, Sarakanuru Krishnappa; Shetty, Ananya (Indian journal of dental research, 2025)
Developing methodological approaches and instrumentation in psychological research is critical since the variables and constructs in the field are diverse and must be assessed with appropriate instruments. Each instrument produced or altered must undergo content validation. The content validation method involves a readability test to determine whether the questions or items accurately represent the assessed constructs or variables. This study aimed to illustrate the steps involved in content translation, adaptation, and validation of Mindful Attention Instruction Script (MAIS) as a novel behavior management technique during local anesthesia procedures in children 9-12 years old exhibiting dental fear and anxiety. MAIS was subjected to various steps to assess its content validity which included, obtaining consensus from the panel of experts, back translation of the script by a subject matter expert, adaptation of the MAIS, preliminary pilot testing for the target group, and conducting content validation. MAIS achieved a satisfactory content validity score of 0.9 and interrater agreement of 0.8. This study showed acceptable levels of validity in the Kannada and Hindi translated versions, illustrating a valid and reliable tool to be used for the evaluation of MAIS that applies to the Indian population.